Multi-scale chromatin state annotation using a hierarchical hidden Markov model - Eugenio Marco (Nature Portfolio, 2017)
The impact of chromatin structure on gene expression makes it integral to our understanding of developmental and disease processes. Here, the authors introduce a hierarchical hidden Markov model to systematically annotate chromatin states at multiple length scales, and demonstrate its utility for the elucidation of the role of chromatin structure in gene expression.